Masouras, Panicos - (:unkn) unknown (My University, 2026)
Panicos Masouras is Senior Lecturer at the Department of Nursing, School of Health Sciences. He holds a BSc degree from the State University of New York at Albany (1985) and an MSc in Information Systems (1996) from the University of Kingston. He worked as Lecturer (1989 – 2002) and as Senior Lectured (2002 – 2007) at the Computer Studies Department of the Higher Technical Institute. He specializes in information systems and data management. His research interests focus on e-health and e-inclusion policies, e-Learning, e-Skills and e-Assessment.
Keywords: Health Informatics; Heath Information Management; Bioengineering; Biomedical Engineering; e-Learning